Analysis on the prokaryotic microbiome in females and embryonic cell cultures of rhipicephalus sanguineus tropical and temperate lineages from two specific localities in brazil - Luzzi, Mayara de Cassia [UNESP]; de Carvalho, Lucas Amoroso Lopes [UNESP]; Pinheiro, Daniel Guariz [UNESP]; Lima-Duarte, Leidiane; Camargo, Jaqueline Valéria [UNESP]; Kishi, Luciano Takeshi [UNESP]; Fernandes, Camila Cesário [UNESP]; Machado, Rosangela Zacarias [UNESP]; Soares, João Fábio; André, Marcos Rogério [UNESP]; Barros-Battesti, Darci Moraes [UNESP] (FapUNIFESP (SciELO), 2021)
Two lineages of Rhipicephalus sanguineus are known in Brazil: the temperate or southern and the tropical or northern populations. The distribution patterns of both lineages of R. sanguineus have epidemiological implications that can affect vectorial competence concerning Ehrlichia canis, the agent of canine monocytic ehrlichiosis. Intending to identify the microbiomes of both lineages and compare microorganisms in R. sanguineus, we used the 16S rRNA (V4-V5 region) gene-based metataxonomic approach, through NGS sequencing on the MiSeq Illumina platform. We selected specimens of females from the environment and samples of primary embryonic cell cultures, from both lineages, and this was the first study to investigate the prokaryotic microbiome in tick cell cultures. The results showed that many bacterial taxa detected in the samples were typical members of the host environment. A significant diversity of microorganisms in R. sanguineus females and in embryonic cell cultures from both lineages was found, with emphasis on the presence of Coxiella in all samples, albeit in different proportions. The Coxiella species present in the two lineages of ticks may be different and may have co-evolved with them, thus driving different patterns of interactions between ticks and the pathogens that they can harbor or transmit to vertebrate hosts.
Análise do microbioma procarionte de fêmeas e cultura celular embrionária de rhipicephalus sanguineus linhagens tropical e temperada de duas localidades no brasil
Keywords: Brown dog tick; Coxiella; Endosymbionts; Temperate lineage; Tick embryonic cell culture; Tropical lineage